Implementation of Character Education Through Extracurricular Pencak Silat (AJER: Advanced Journal of Education and Religion, 2024)
This research is motivated by juvenile delinquency and promiscuity, which hurts students' character. This research takes the title of implementing character education through extracurricular martial arts. This type of research is qualitative with a descriptive model, data collection techniques using observation, interviews, and documentation, and data analysis used are data reduction, data exposure, and verification. Based on the results of the research that has been done, it can be concluded that: 1. The process of character education goes through several stages, namely: The first stage is a trainer providing explanations or providing basic material knowledge, spiritual material, motivation, and advice. In the second stage, a trainer invites students to conduct positive activities through words and actions. This stage is also called the value transaction stage. The third stage is the transinternalization of values. Namely, students are required to implement or practice character values in everyday life. 2. The results of implementing character education through the pencak silat extracurricular are well implemented and produce the character values of purity, responsiveness, and tanggon.